PENURUNAN KONSOLIDASI EMBANKMENT DI ATAS TANAH LEMPUNG LUNAK - Agus Setyo Muntohar (Jurnal Semesta Teknika UMY, 2004)
The soil settlement can be easily calculated based on the Boussineqs’ theory. However, the approximate method has some limitation when applied in different soils. In this study, a simple model of embankment over the soft clay soils is devised to study the settlement characteristics. The model is scaled as length dimension (L) 1 : 10, whose fabricated from flexiglass material and rigid. The clay thickness is varies in two different layers i.e. 10 cm (P-1) and 20 cm (P-2). Consolidation test is carried out to investigate the compressibility properties of clays used in the model. The settlement was analyszed by using analyhitcal method: one-point, 1/6 Simpson, dan sub-layers methods. The test result shows that the sub-layers method is accurate to calculate the consolidation settlement compared to other two methods. The number of layers as much as n = 20 is enough to calculate the settlement convergency. The accuracy of the sub-layers method is confirmed also when compared to result of embankment model. In general, the sublayers method is more applicable to calculate the consolidation settlement of the soft clay whose the clay thickness is equal or greater than width of the foundation (Bf).